SCIENCE AND TECHNOLOGY (IPTEK) FOR FARMER GROUPS THAT ARE LOCATED IN CRITICAL LAND IN ANTICIPATION OF LAND RUPTURE OF BATU CITY. - Hirijanto Hirijanto; Sudirman Indra (STIE Malangkucecwara, 2018)
Watershed (DAS) of the upstream part of Kali Brantas, especially the catchment areas for the conservation in the lower part has experienced a decrease in production, especially the area of ​​Batu City as an agropolitan city has grown in such a way from year to year, so its main function as the rainwater absorption area increasingly reduced. This is due to the changing conditions of water catchment areas into agricultural land and settlements. Changes in land use conditions lead to land degradation, which is potentially catastrophic: landslides, erosion, floods, droughts and reduced water source discharges. Damage to water resources can not be separated from environmental damage in the vicinity such as land damage, vegetation and population pressure. These three matters are interrelated in influencing the availability of water resources. Identification of critical lands by Geographic Information System (GIS) method is expected to obtain valid and valid results. Based on the problems described above, the proposed solution is Land Conservation by vegetation and mechanical means. In the first method with vegetation, there are two mechanisms used: root systems and organic materials condition the growth of organisms that naturally create bio pores, thus increasing the porosity of the soil. Thus the soil recharge capacity will increase. In the second method mechanical is by making terras perpendicular to the slope line so that inhibits the erosion, which can lead to slope slope and the loss of nutrients in the soil